Cooperative control method of seed and fertilizer simultaneous sowing of electric drive peanut planter - Yu, Yan; Wang, Xiaomin; Wang, Xiaomin; Wang, Xiaomin; Shang, Shuqi; Shang, Shuqi; Tan, Xiaozhi; Yi, Dazhi; Shang, Shuqi; Tan, Xiaozhi; et al. (International Journal of Agricultural and Biological Engineering, 2025)
Aiming at the problems of low intelligence level of peanut seeder, unstable quality of sowing and fertilization, and poor coordination ability of one-time multi-work, this paper proposes a cooperative control method for simultaneous sowing and fertilization in electric-driven peanut planters. In this method, an improved cross-coupling control structure is proposed to realize the cooperative control of sowing and fertilization, and a fuzzy PID controller is designed. In addition, in order to solve the problem of high overshoot and poor system follow-up when the target speed of the control motor changes greatly during the operation process, an improved particle swarm optimization algorithm is introduced to reduce overshoot, improve response speed, and improve the control accuracy and stability of the seed and fertilizer simultaneous sowing control system. The method was simulated and analyzed on the Matlab/Simulink simulation platform, and the simulation results indicate that the dynamic performance and anti-interference capability of the improved controller have been significantly enhanced. To verify the effectiveness of this control method, an experiment on simultaneous sowing and fertilization of peanuts was designed. The experimental data showed that under stable operation, the average sowing qualification rate was 98.67% and the average fertilization qualification rate was 98.34%; under sudden load conditions, the average sowing qualification rate was 97.33% and the average fertilization qualification rate was 98.18%. The method maintained a low fluctuation range under different working conditions, effectively achieving precise simultaneous sowing and fertilization of peanuts. This research can provide effective technical reference for efficient peanut cultivation. Key words: simultaneous sowing and fertilization; IPSO algorithm; improved cross-coupling structure; control system DOI: 10.25165/j.ijabe.20251806.9547 Citation: Yu Y, Wang X M, Shang S Q, Tan X Z, Yi D Z, Dong W K, et al. Cooperative control method of seed and fertilizer simultaneous sowing of electric drive peanut planter. Int J Agric & Biol Eng, 2025; 18(6): 212–220.